2021
DOI: 10.1017/s1368980021003827
|View full text |Cite
|
Sign up to set email alerts
|

Trends and factors associated with the nutritional status of adolescent girls in Ghana: a secondary analysis of the 2003–2014 Ghana demographic and health survey (GDHS) data

Abstract: Objective: We examined the trends-over-time and the factors associated with malnutrition among adolescent girls in Ghana. Design: Cross-sectional analysis from 3 nationwide Ghana Demographic and Health Surveys conducted in 2003 (n=983), 2008 (n=955) and 2014 (n=857). We used Cox proportional hazard models with sample weighting to model the prevalence ratio (PR) of malnutrition. Setting: Countrywide, covering rural and urban areas in Ghana. Subjects: No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Malnutrition is a complex phenomenon characterised by a multiplicity of factors ranging from the socioeconomic status to dietary intake, water, sanitation and hygiene (WASH) practices, and socio-political factors affecting policymaking (3)(4)(5) . Addressing the adolescent nutrition is fundamental to materialise the potential human capital gains and to break the intergenerational malnutrition trap.…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition is a complex phenomenon characterised by a multiplicity of factors ranging from the socioeconomic status to dietary intake, water, sanitation and hygiene (WASH) practices, and socio-political factors affecting policymaking (3)(4)(5) . Addressing the adolescent nutrition is fundamental to materialise the potential human capital gains and to break the intergenerational malnutrition trap.…”
Section: Introductionmentioning
confidence: 99%
“…Explanatory variables were classified as individual and community-level factors. Explanatory variables were Socioeconomic, demographic, and Environmental factors were selected based on previous studies and their availability in the DHS dataset [21][22][23][24][25]. Individual level variables considered in this study were age, marital status, educational status, sex of head, number of under-five, current working status, breastfeeding, religion, relationship to head, age of household head, wealth index, source of drinking water, time to get to a water source, and latrine.…”
Section: Study Variables and Definitionsmentioning
confidence: 99%
“…The study in Mexico focused on adolescent girls and boys aged 12–19 years and showed that both a Western- and plant-based dietary pattern were simultaneously associated with overweight–obesity and at least one indicator of under-nutrition such as anemia [ 192 ]. In Ghana, time trends in anthropometry in adolescent girls aged 15–19 years showed that thinness and stunting had declined since 2003, but that the prevalence of overweight and obesity had increased by 40%, while anemia remained severe [ 11 ]. There is a double burden of malnutrition as evident in this vulnerable group, and becoming even more prominent, suggesting that obesity and anemia can co-occur in the same girls, which needs to be taken into account in dietary advice and nutrition programs.…”
Section: Introductionmentioning
confidence: 99%